Pelatihan Kreasi Jajanan Unik: Nugget Nanas dan Pastel Nanas Untuk Pemberdayaan UMKM Desa Kuta - Apriyani, Delta; Barokah, Annisa Khoirul; Wibowo, Keisha Frandhea Arinka; S, Sainah (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Kuta Village, located in Belik District, Pemalang Regency, has superior potential in the agricultural and plantation sectors, especially pineapple. However, local people still sell pineapples in their raw state, which causes their selling value to be low. To increase the economic value of pineapple, Community Service (KKN) students from Semarang State University (Unnes) held innovative training for Kuta Village residents, especially mothers in Kuta Village. This training focused on processing pineapple into snacks such as pastels and pineapple nuggets, which was held at the UNNES GIAT 9 KKN Post in Kuta Village. This training invited speakers from the pineapple farmer group in Beluk Village who demonstrated it directly to the mothers in Kuta Village. As a result, around 95% of participants showed high enthusiasm by actively asking questions about the ingredients and how to make the product. This innovation received a positive response and has the potential to be developed as a sustainable program to encourage the growth of Micro, Small, and Medium Enterprises (MSMEs) in Kuta Village, so that it can increase the independence and welfare of the village community